Optimization of Photos and Videos as Science Media in Elementary Laboratory of Gorontalo State University - Nurfahmi Moligai (Journal of Educational Technology and Innovation, 2026)
This study aims to determine the use of photo and video media in science learning at Elementary School Laboratory of Gorontalo State University, the role of photo and video media in helping students understand science learning materials at Elementary School Laboratory of Gorontalo State University and teachers' strategies in utilizing photo and video media to support science learning at Elementary School Laboratory of Gorontalo State University. This study uses a qualitative approach. The data collection technique is to conduct observations and interviews with teachers at the Laboratory Elementary School of Gorontalo State University. The results of the study show that the use of photos and videos can increase learning motivation, student involvement, and understanding of learning materials in a more interesting and easy-to-understand way. Visual media is also considered very relevant to the characteristics of students, including students with special needs, because it is able to create a more active, inclusive, and fun learning environment. In addition, teachers utilize various digital learning platforms such as Canva, Quizizz, and Nearpod to support the implementation and evaluation of visual media-based learning. However, there are several obstacles in its implementation, especially related to the instability of the internet connection. However, school facilities, teacher competence, and the implementation of learning strategies such as Project-Based Learning (PBL) support the effective use of these media.